Kinematography of a city: moves into drawing - Banou, Sophia Konstantina (The University of Edinburgh, 2016)
This thesis aims to explore the temporal and material limits of architectural drawing through the question of urban representation. Challenges posed by the latter are used to put pressure on the fixity of drawing conventions, in order to expand architectural drawing’s range of concerns to the transitory conditions of space that emerge between order and event. Since the eighteenth century, the city has acted as the ground and mirror of the productive, economic, social and epistemological breaks and turns that have marked the passage to modernity. This radical transformation of the city and its modes of experience and inhabitation, combined with the visual culture that has since emerged, have raised questions of presence and representation with regards to both the city and its image in architectural drawing. This thesis aims to bring these questions into the frame of the current concerns in architectural representation, following the deconstructive and cartographic approaches that emerged in the latter half of the twentieth century and the effects of a rising virtuality. As the understanding of space has shifted from the idea of an a priori extensity of vacuum versus matter to a dynamic multiplicity of relations, respectively architectural representation is understood as itself a transaction: a complex oscillation between the real and the mental. This research becomes concerned with exploring drawing as a situated experience that involves the inhabitation of both the space of the city and the drawing. Such a consideration of drawing as a distinct spatiality consequently brings to the fore a dynamic and productive reciprocity between the city and its representation. In order to engage with the intangible projective spatiality of drawing and the negotiations that take place in the movement of representation, the thesis examines the processes involved in the representation of the urban through the immersive site-specificity of installation. Installation is proposed as a way of drawing in space, and thus of foregrounding the question of the space of drawing. The thesis unfolds as a movement across the space of drawing, through a series of essays and corresponding installations which cumulatively form a survey of a city, while performing a close inquiry into the agency of the distinct elements of drawing. Edinburgh serves as both the object and the place of performance, the testing ground, for this act of observation and representation.
Keywords: architecture; drawing; urban representation; installation; notation; motion; movement